2016
DOI: 10.1155/2016/9208035
|View full text |Cite
|
Sign up to set email alerts
|

Association of Complement Receptor 2 Gene Polymorphisms with Susceptibility to Osteonecrosis of the Femoral Head in Systemic Lupus Erythematosus

Abstract: Osteonecrosis of the femoral head (ONFH) is a complex and multifactorial disease that is influenced by a number of genetic factors in addition to environmental factors. Some autoimmune disorders, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and inflammatory bowel disease (IBD), are associated with the development of ONFH. Complement receptor type 2 (CR2) is membrane glycoprotein which binds C3 degradation products generated during complement activation. CR2 has many important functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…However, the genetic predispositions associated with ON susceptibility in SLE patients, including ancestry effects, have not yet been demonstrated. Polymorphism of T786C NOS3 in the promoter was associated with idiopathic ON 128 but not with ON in SLE patients, 123 suggesting the influence of different ethnic groups on genetic variation. Investigation of the prevalence of genetic risk factors associated with ON susceptibility in both the general population and in patients of varying ancestries, is a consideration for a future study.…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 95%
See 2 more Smart Citations
“…However, the genetic predispositions associated with ON susceptibility in SLE patients, including ancestry effects, have not yet been demonstrated. Polymorphism of T786C NOS3 in the promoter was associated with idiopathic ON 128 but not with ON in SLE patients, 123 suggesting the influence of different ethnic groups on genetic variation. Investigation of the prevalence of genetic risk factors associated with ON susceptibility in both the general population and in patients of varying ancestries, is a consideration for a future study.…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 95%
“…Kim et al have identified that Asp258Asp (exon 6: rs1549758) and Glu298Asp (exon 7: G895T: rs1799983) polymorphisms in the nitric oxide synthase 3 (NOS3) gene may be related to ON susceptibility in SLE patients under the recessive model. 123 A case-control study demonstrated that rs3813946 in the 5′-UTR, rs311306 in intron 1, and the rs17615 in exon 10 of the CR2 (complement receptor type 2, complement C3d Receptor 2) gene. 124 A recent study has also identified that SNPs for ON risk in SLE patients include NOS3 (exon 6: c.814G > A, p.E272K), Collagen Type II Alpha 1 Chain (COL2A1, c.3508G > A, rs41263847: exon 29: c.1913C > T: p.T638I, exon 28: c.1706C > T: p.T569I, and rs371445823: exon 8: c.580G > A: p.A194T, exon 7: c.373G > A: p.A125T), 125 and CR2 (rs45573035: exon 2: c.200C > G: p.T67S).…”
Section: Risk Factors For the Development Of On In Patients With Slementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that single nucleotide polymorphisms (SNPs) are associated with an increased risk of ONFH [ 19 22 ]. The polymorphisms of MMP8 have been investigated in many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study demonstrated that CR2 could bind C3 degradation products during complement activation, 10 suggesting that CR2 might play an essential role in immunity. 11 Additional studies showed that polymorphisms of the CR2 gene were associated with osteonecrosis in SLE 12 and that polymorphisms such as rs3813946, rs1048971, and rs17615 were associated with lupus susceptibility in Caucasian and Chinese lupus patients. 13 Next-generation sequencing technologies have been widely used for sequencing exomes, transcriptomes, and genomes, 14 particularly in the mutant landscape of genetic diseases.…”
mentioning
confidence: 99%